Legal frontiers in education complex law issues for leaders, policymakers and policy implementers - Normore, Anthony H. (Bingley, U.K. : Emerald, 2015)
This book examines issues in educational law and the way leaders, policymakers and policy implementers influence just processes and outcomes in schools. From the lens of professors, attorneys and administrators we explore how lessons learned from the authors' experiences and research might improve the preparation and practice of educational leaders. We examine how leaders can and should be conceived as advocates for justice, especially those with positional power and formal influence. Educational law has both conceptual and empirical qualities. While research on justice often begins with abstract conceptualizations, it is also manifest as tangible and observable activities and behaviours. Thus it follows that law can be studied through a variety of methodological approaches. Depending on the epistemological and/or methodological orientation of a study, justice may be a measurable or observed event, a purely theoretical construct, or a combination of both. Leaders must address questions about law and justice. Of equal importance is how to navigate complex legal issues and how to best engage in the decision-making processes while keeping the best interests of students at the fore.
Inconsistencies across the states : an examination of anti-bullying laws / James Vines -- Recent litigation and guidance involving bullying of students with disabilities / Janet R. Decker, Suzanne E. Eckes -- From student armbands to cyberbullying : the first amendment in public schools / Kathleen Conn -- A portrait of the legal barriers to the education of immigrant children : an analysis of state statutes and national initiatives / Chinasa A. Elue, Patricia F. First -- Academic language development : barriers to success for multilingual language learners / Caron Mellblom-Nishioka -- A litigation trend analysis of case law outcomes pertaining to the educational rights of English learners : a civil rights issue / Delia E. Racines -- Navigating the current legal landscape of the identification and eligibility of children with autism spectrum disorder / Kevin P. Brady, Cynthia A. Dietrich -- The relationship between community educational attainment and the discipline implementation of fourth amendment legal principles in public schools / Jeffrey Burke, Mario Torres -- Educational administration in Indian country : the peculiar position of indigenous languages, tribal self-determination, and federal policy / Hollie J. Mackey -- Hope for homeless youth : the McKinney-Vento act and the promise of educational access and opportunity / Susan C. Bon, Nicole D. Snyder -- To protect and educate : legal mandates and complex leadership of school resource (police) officers / Anthony H. Normore ... [et al.] -- Fraser and the cheerleader : values and the boundaries of student speech / Patricia A.L. Ehrensal -- When equality is not equity : regional cost differences and the real allocation of educational resources / Lori L. Taylor -- Collective bargaining : policy tensions and practical options for school leaders / Mark Paige.
Includes index.
Print version record
Keywords: Education -- Educational Policy & Reform -- General; Education; Educational strategies & policy; Organization & management of education; Educational law and legislation